ADEA‐ADEE Shaping the Future of Dental Education III: From interprofessional education to transprofessional learning: Reflections from dentistry, applied linguistics, and law. Issue 1 (24th January 2020) - Field, James; Hervey, Tamara; Walsh, Steve; Davis, Joan; Garcia, Lily T.; Valachovic, Richard W.
Abstract: The World Health Organization has indicated that Interprofessional Education (IPE) occurs when "students from two or more professions learn about, from, and with each other". 1 These IPE experiences are widely thought to provide students with the opportunity to learn and practice the knowledge, skills, behaviors and attitudes that will ultimately translate into the provision of safer, higher quality, team‐based patient care when they become health care practitioners in collaborative care environments. At the joint American Dental Education Association (ADEA) and Association for Dental Education in Europe (ADEE) 2019 Shaping the Future of Dental Education III conference in Brescia, Italy, delegates explored the concept of transprofessional learning, where students learn skills across a wider range of professions than health professions alone. The workshop continued the dialogue that began during the 2017 ADEA‐ADEE Shaping the Future of Dental Education II conference in London, England as previously reported by Davis et al., 2 and explored the use of transprofessional learning through the lenses of dental education, applied linguistics education and law education focusing on the use of reflective practices. The workshop brought together educators from around the globe in a highly interactive setting where they had the opportunity to discuss and develop tools and practices for teaching reflective practice by using a transprofessional learning approach.